Sodium oxybate for the maintenance of abstinence in alcohol-dependent patients: An international, multicenter, randomized, double-blind, placebo-controlled trial. (October 2022) - Guiraud, Julien; Addolorato, Giovanni; Antonelli, Mariangela; Aubin, Henri-Jean; de Bejczy, Andrea; Benyamina, Amine; Cacciaglia, Roberto; Caputo, Fabio; Dematteis, Maurice; Ferrulli, Anna; Goudriaan, Anna E; Gual, Antoni; et al.
Background: Sodium oxybate (SMO) has been shown to be effective in the maintenance of abstinence (MoA) in alcohol-dependent patients in a series of small randomized controlled trials (RCTs). These results needed to be confirmed by a large trial investigating the treatment effect and its sustainability after medication discontinuation. Aims: To confirm the SMO effect on (sustained) MoA in detoxified alcohol-dependent patients. Methods: Large double-blind, randomized, placebo-controlled trial in detoxified adult alcohol-dependent outpatients (80% men) from 11 sites in four European countries. Patients were randomized to 6 months SMO (3.3–3.9 g/day) or placebo followed by a 6-month medication-free period. Primary outcome was the cumulative abstinence duration (CAD) during the 6-month treatment period defined as the number of days with no alcohol use. Secondary outcomes included CAD during the 12-month study period. Results: Of the 314 alcohol-dependent patients randomized, 154 received SMO and 160 received placebo. Based on the pre-specified fixed-effect two-way analysis of variance including the treatment-by-site interaction, SMO showed efficacy in CAD during the 6-month treatment period: mean difference +43.1 days, 95% confidence interval (17.6–68.5; p  = 0.001). Since significant heterogeneity of effect across sites and unequal sample sizes among sites ( n  = 3–66) were identified, a site-level random meta-analysis was performed with results supporting the pre-specified analysis: mean difference +32.4 days, p  = 0.014. The SMO effect was sustained during the medication-free follow-up period. SMO was well-tolerated. Conclusions: Results of this large RCT in alcohol-dependent patients demonstrated a significant and clinically relevant sustained effect of SMO on CAD. Trial registration: ClinicalTrials.gov Identifier: NCT04648423